“I Am Excessively Pressed by Classroom Tasks”: A Cross‐Cultural Study on the Sources and Solutions of Chinese and Iranian EFL Students' Academic Disengagement in Online Classes - Derakhshan, Ali; Gao, Xuesong (Andy) (Psychology in the schools, 2025)
ABSTRACT Online education may induce different negative emotions and emotional reactions in language learners. One such reaction emerging from emotional experiences in online contexts is academic disengagement, which has been limitedly examined in L2 research. To fill this lacuna, this study has been done to probe into the sources and solutions of student disengagement in online L2 classes from the perspective of Chinese and Iranian students. To accomplish this, through maximum‐variation sampling, a sample of Chinese (n = 164) and Iranian (n = 150) students was selected to take part in this inquiry. Then, an open‐ended questionnaire was virtually distributed among participants. Participants' answers to the open‐ended questions were thematically analyzed using MAXQDA software. The findings of the thematic analysis reveal that both Chinese and Iranian L2 learners had a similar view of the sources of academic disengagement considering the outcome of different online‐related, teacher‐related, learner‐related, and course/task‐related issues. The findings also show that the majority of Chinese and Iranian L2 learners attribute student academic disengagement to online‐related issues, including limited face‐to‐face interactions, technological breakdowns, and a boring learning atmosphere. To address the issue of student disengagement, the participants of both contexts report three broad categories, namely teacher‐related, student‐related, and administrator‐related solutions. The solutions offered by the participants imply that both Chinese and Iranian L2 learners hold students, teachers, and educational administrators responsible for student disengagement in online classes. The findings may help L2 instructors and educational managers respond to student disengagement in online language classes effectively. Summary Online education involves various emotions and emotional experiences, which can considerably influence the process of second/foreign language (L2) education. Such emotional states are significant to be covered in teacher training courses so that teachers can regulate them effectively. Chinese and Iranian L2 students proposed similar sources for online academic disengagement. They considered it as the outcome of different online‐related, teacher‐related, learner‐related, and course/task‐related issues. This similarity may encourage the quest for a universal framework for regulating learner disengagement in online education. The participants found students, teachers, and educational administrators responsible for managing and regulating academic disengagement in online classes. This highlights the prominence of a collective practice to tackle academic disengagement.